SOSIALISASI PENDAMPINGAN PENDAFTARAN MEREK TERHADAP USAHA MIKRO KECIL DAN MENENGAH SEKITAR CILANDAK BARAT - Ramadhan, Niko Rafael; Saputra, Septian Sugiarta; Oktaviana, Dina; Simajorang, Dianingtas Hartono; Zalsabilla, Zara Zyasky; Febridha, Salsabillah; Deswita, Adelia; Nurdin, Aulia Anjani; Nadjima, Aulia Rachmatullah; Andhiyo, Immanuel Given Bintang; Ramadhan, Aditya Rizky; Darussalam, Rezky Fabyo; Rasyad, Pasha Athallah; Hadhani, Muhammad Gading Bintang; Tambunan, Daniel; Harley, Airiique Bintang Merah; Zulfikar, Faiz Raudhin; Winata, Henry; Bachtiar, Muhammad Rizky; Akbar, Maulana Muhammad; Putro, Alberto Muhammad Gusti (Zhata Institut, 2025)
Intellectual property rights are a guarantee of maintaining one's basic intellectual rights. Trademark as an intellectual property right is very important but there are still many MSMEs that have not registered a trademark because they do not understand the importance of a trademark or do not understand how to register it. This service is carried out to help MSMEs understand more about the registration and importance of brands. The location of the MSME partner that is the target of the service is in South Jakarta called MAW Juice, the location was chosen because this service aims to benefit the area around the University of the service team. These MSME partners have problems registering brands that have previously been tried but rejected due to a lack of understanding of brand registration procedures. The method of implementing activities is counseling, namely providing useful material to help provide insight and guidance in registering trademarks and dialoguing with presenters to better understand brands and accompany MSME partners in registering Trademark Rights at the DJKI. The service team succeeded in conducting counseling that increased understanding of the importance of brand registration and how to register brand procedures. The service team also succeeded in accompanying MAW Juice MSME partners in registering trademarks at the DJKI.